PENGARUH DANA BAGI HASIL (DBH) PAJAK DAN BELANJA OPERASI TERHADAP SISA LEBIH PEMBIAYAAN ANGGARAN (SILPA) (Studi kasus pada Dinas Pendapatan dan Pengelolaan Keuangan (DPPK) Kabupaten Bandung) - Muhammad Iqbal; Nina Mulyani (AKURAT | Jurnal Ilmiah Akuntansi FE UNIBBA, 2016)
This study aims to test hypotheses related to the influence of the variables of Tax Product Shared Fund and Operating Expense to Budget Surplus Financing (SILPA). This study consists of three (3) variables, Tax Product Shared Fund(X1), and Operating Expense (X2) as independent variables, and Financing Budget Surplus (SILPA) (Y) as the dependent variable. Tax Product Shared Fund is one of revenue derived from the State Budget. Operating expense is one of the shopping areas are used to meet the operational needs of the government. Financing and Budget Surplus (SILPA) is surplus between actual income and expenditure, as well as revenues and expense in the state budget funding / budgets during the reporting period. The method used in this research is descriptive associative method with a case study approach. Quantitative data used in this study was obtained from the Budget Reports for 5 (five) years from the year 2008 to the year 2012 Statistical tests were used to process data in this research is multiple linear regression. The results showed that the partial correlation between the Tax Product Shared Fund to Budget Surplus Financing (SILPA) amounted to 0,142 which means it has a very low correlation. While the partial correlation between the Operating Expense to Budget Surplus Financing (SILPA) is 0,501, which means having a relationship that is being. And for simultaneous correlation betwee the Tax Product Shared Fund and Operating Expense to Budget Surplus Financing (SILPA) is 0,631 which means it has strong relationship. Based on hypothesis testing, there was no significant effect between theTax Product Shared Fund and the Operating Expense to Budget Surplus Financing (SILPA) either partially or simultaneous. As for the effect of Tax Product Shared Fund and Operating Expense to Budget Surplus Financing (SILPA) is very low at 39.8%, while the remaining 60.2% is influenced by other factors that are not addressed in this study such as revenue (Silpa), Other Expense than Operating Expense, Local Financing, and others